Identifikasi Kerusakan Mobil City Car Automatic dengan Pendekatan Backward Chaining System Pada Auto2000 Pandeglang - Neli Nailul Wardah; Agung Sugiarto; Aghy Gilar Pratama (Ikatan Ahli Informatika Indonesia, 2019)
City Car Automatic is one of the four-wheeled land transportation vehicles that includes vehicles that meet the standards set by the government, namely Fuel-Saving Motor Vehicles at affordable prices or better known as Low Cost Green Car (LCGC). In addition, its small and agile enough to drive on a crowded road and easy to park and its ease of operation is the reason for people to choose this type of car. Auto2000 is the largest Toyota retailer network in Indonesia, which always strives to provide the best service for all of its customers including after sales service services in accordance with its slogan